Laporan Kasus : Abses Gingiva Akibat Traumatik Oklusi pada Pasien Pasca Kehamilan - Nidha Tuhu Respati Karno; Dewi Muflikhah; Budi Yuwono (Fakultas Kedokteran Gigi Universitas Jember, 2018)
Gingival abcess is apurulent inflamation that localized in periodontium. Clinically manifested start with toothache, swelling and redness gingiva, fistule gingiva, which can include malaise and headache. Woman during pregnancy could have gingivitis more easily and getting worse with traumatic occlusion. A women 27 years old came with the swelling chin since ± 3days ago. The swelling is painful, with toothache, swelling dan redness gingiva, fistule gingiva, andmalaise. The final diagnose in this case is gingival abcess.